2019
DOI: 10.1177/0891988719874130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Anxiety in Parkinson Disease and Impact on Quality of Life: A Community-Based Study in Spain

Abstract: Background: Identifying neuropsychiatric disorders is essential for prompt treatment to reduce morbidity. Among these disorders, anxiety and depression have been frequently associated with Parkinson disease (PD), particularly among elderly population. Objective: The objective of this study is to determine the prevalence of anxiety and depression in a series of community-based PD cases in Spain, their relationship with different clinical and sociodemographic characteristics, and quality of life. Methods: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 27 publications
5
49
0
2
Order By: Relevance
“…This is in line with prevalence of anxiety among patients with PD by Broen et al and Leentjens et al ranging from 24.5 to 46.7 with GAD as the most common single disorder and 31.1% having mixed anxiety disorder [34,35]. In Egypt, Ragab and colleagues report anxiety prevalence around 30% [27], while in Spain and France the prevalence was 68.7% and 51%, respectively [30,31]. On the other hand, a Chinese study found the prevalence was much lower than others around 25.8% [36].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in line with prevalence of anxiety among patients with PD by Broen et al and Leentjens et al ranging from 24.5 to 46.7 with GAD as the most common single disorder and 31.1% having mixed anxiety disorder [34,35]. In Egypt, Ragab and colleagues report anxiety prevalence around 30% [27], while in Spain and France the prevalence was 68.7% and 51%, respectively [30,31]. On the other hand, a Chinese study found the prevalence was much lower than others around 25.8% [36].…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, Ragab and colleagues found the prevalence at 47.5% [27]. Across literature, several studies [7,[28][29][30][31] found the prevalence of depression in PD was ranging from 32.6 to 41%. A systematic review conducted by Reijnders et al reported that 17% and 22% of PD patients had MDD and minor depression, respectively [32].…”
Section: Discussionmentioning
confidence: 99%
“…Complete description of the study was provided to participants before entering the survey by telephone call. The patients who had any medical history of psychosis or a Mini-Mental State Examination (MMSE) score of ≤ 12 were excluded from the study [8]. For the control group, the questionnare was broadcasted over Wechat public messenger platform, commonly used in the country.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with ASD show a prevalence of anxiety in 39.6% [ 45 ], depression in ~30% [ 46 , 47 , 48 , 49 ], and OCD in 17.4% of cases. In PD, the prevalence of anxiety is described in 65–68.42% [ 50 , 51 ], depression in 13.8–56% [ 50 , 51 , 52 ], OCD in 37.5% (drug naïve) [ 53 ], and impulse control behavior (ICB) in 17.1–28.6% [ 54 , 55 ] of patients with PD. ICB in PD is illustrated by gambling, compulsive eating, punding, excessive shopping, or hypersexuality.…”
Section: Overlapping Clinical Motor and Behavioral Phenomenology Bmentioning
confidence: 99%